Europa in Wonderland: Gobling Market or Sappho's Gymnasium - Douka Kabitoglou, Ekaterini (Miscelánea: A Journal of English and American Studies, 2004)
Europa, the ‘godmother’ of Europe, operates as a hostess and ‘instructor’ in the diachronic journey over the European pedagogic landscape that is attempted in this presentation, initiating us into an adventure in the educational wonderland which begins at the topos of her ‘adopted’ country: Greece. Taking for granted that for the Greeks education was based on a profound relationship between two people, one young and the other mature, who was at once model, guide and initiator, and moreover that it adopted a cult of the Muses seeking wisdom through an aesthetic and ‘erotic’ approach to life, Sappho and Socrates are introduced as paradigms of the Greek system of schooling. Socrates’ educational ‘opponents’, the Sophists, are seen as the founders of utilitarianism, forerunners of the modern commercialism of education.Christina Rossetti’s poem Goblin Market is used (because of its multi-layered title suggesting the triumph of a ‘commodity’ morality) as the bridge to carry us to the present condition of the European university. Tracing the steps that have led to the formation of the European Higher Education Area, the presentation highlights the gradual transformation of education from a public ‘good’ to a marketable ‘product’. Attending to voices of dissent (expressed by members of ESSE) and setting the whole problem in a larger philosophical context, we can hear a Socratic echo in Heidegger, Gadamer, and Derrida who profess the ‘questioning’ attitude as the only form of knowledge. Hoping that ‘memory’ may reveal forgotten signs from the past to guide us through the schizoid split tormenting today’s academy, we return with Olga Broumas to “Sappho’s Gymnasium” lest that ‘maternal’ presence may give/be the answer.
Keywords: Education; Eros; Greece; Question; University